Jain point: A new safe portal for laparoscopic entry in previous surgery cases - Nutan Jain; Sweta Sareen; Swati Kanawa; Vandana Jain; Sunil Gupta; Sonika Mann (Wolters Kluwer Medknow Publications, 2016)
INTRODUCTION: The present study was performed to assess the safety and feasibility of a new laparoscopic entry site in cases suspected of adhesions due to previous surgery. MATERIALS AND METHODS: It is a retrospective study undertaken at a tertiary care referral center for advanced gynecological laparoscopic surgery from January 2011 to December 2014. RESULTS: In 624 patients with a history of previous abdominal surgeries, the laparoscopic entry site was through a newly devised point. It is a point in the left paraumbilical region at the level of umbilicus, in a straight line drawn vertically upward from a point 2.5 cm medial to anterior superior iliac spine. Intra-abdominal adhesions were found in 487 (78.0%) patients, and umbilical adhesions in 404 (64.7%) patients with past abdominal surgeries. CONCLUSION: There were no significant entry-related, intra-operative, or postoperative complications with the use of this entry point. It is also suitable as a main working port during the course of surgery.